By His Excellency Jonathan Belcher, Esq; captain general and governour in chief, in and over His Majesty's province of the Massachusetts-Bay ... A proclamation for a publick thanksgiving : ... Thursday the thirteenth day of November next ... Given at the Council chamber in Boston, the twentieth day of October 1740 (Printed by J. Draper, printer to His Excellency the governour & Council, 1740)
October 20, 1740 Proclamation by Massachusetts Governor Jonathan Belcher setting November 17th as a day of thanksgiving for the King and his family, and protection from enemies.